FROM ONLINE TO IN-PERSON: STUDENTS’ MOTIVATION AND SELF-REGULATION IN SCIENCE TEACHING ACTIVITIES DURING AND AFTER THE COVID-19 PANDEMIC - Syauqi, Salma Kaisan; Winarno, Nanang; Samsudin, Achmad; Damopolii, Insar; Firdaus, Rohim Aminullah (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
This study aims to find out the differences in students’ motivation and selfregulation in science teaching activities during and after the COVID-19 pandemic and the strengths and weaknesses of science teaching activities during and after the COVID-19 pandemic from students’ perceptions to improve students’ engagement and achievement in science. This study used a survey design involving 469 junior high school students from 7th, 8th, and 9th grades from 30 different schools located in West Java, East Java, West Nusa Tenggara, Central Java, Special Capital Region of Jakarta, Riau, and East Kalimantan. The instrument consisted of an adapted version of the SALES Questionnaire with a 5-point Likert scale and open-ended questions. Data analysis was carried out by quantitative and qualitative methods. The results showed that students’ motivation and self-regulation in science teaching activities during and after the COVID-19 pandemic were significantly different. The strengths of science teaching activities during the COVID-19 pandemic are flexibility, fewer distractions, and the availability of more learning resources, while the weaknesses are a lack of explanation and understanding, uninteresting, limited interaction, and limited practical activities. The strengths of science teaching activities after the COVID-19 pandemic are clearer explanations, availability of practical activities, and ease of interaction, while the weaknesses are distractions from peers, limited learning resources, and boring. The findings from this study provide an opportunity for science teachers to plan and implement effective learning strategies to increase students' motivation and self-regulation to improve their engagement and achievement in science.